Opportunities within the Agri-food System to Encourage a Nutritionally Balanced Diet – Part I. Issue 7 (3rd October 2021) - Van Pamel, Els; Cnops, Gerda; Van Droogenbroeck, Bart; Delezie, Evelyne C.; Van Royen, Geert; Vlaemynck, Geertrui Mml; Aper, Jonas; Muylle, Hilde; Bekaert, Karen Mm; Cooreman, Kris; Robbens, Johan; Delbare, Daan; et al.
ABSTRACT: To meet their growing interest and to counteract the increase of diet-related diseases worldwide, the field-to-fork concept comprises opportunities for providing consumers with nutritious and health-beneficial food. Although health-beneficial effects have been ascribed to specific food compounds, most often in vivo human evidence and/or accepted health/nutrient claims are lacking. Part I of this review gives an overview of possible sources of macronutrients, micronutrients and other compounds (e.g. secondary metabolites) with proven in vivo human health-beneficial effects and/or health/nutrition EFSA claims. More importantly, it focuses on opportunities within the primary production to obtain/increase/maintain sufficient amounts of such compounds: (i) crop choice, breeding, crop husbandry and environment, harvesting/storage for plant-derived products, (ii) breeding stock selection, feeding strategies and animal husbandry for animal-derived products. However, providing food commodities/products with sufficient amounts of such nutrients is one thing, but aspects like, for example, bioavailability and interindividual variability play a role as well. As such, a balanced diet should be aimed at by means of differentiation within the dietary pattern while considering foods as a whole rather than a sum of compounds. Within this concept, all factors/actors of the agriculture-food-health trichotomy should be integrated as much as possible to provide consumers with health-beneficial food commodities/products.